PENENTUAN KUALITAS BUAH NAGA (Hylocereus undatus) DENGAN METODE NON-DESTRUKTIF [Non-destructive Determination of Dragon Fruit (Hylocereus undatus) Quality] - Khuriyati, Nafis; Fibriato, Muh Bayu; Nugroho, Darmawan Ari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2018)
Sorting dragon fruit based on color, size, and physical defects using human senses does not adequately reflect the nutritional content of the fruit. Nutrient content in dragon fruit has been determined by injuring fruit (destructive). The objective of the research was to develop a non-destructive method based on color measurement to determine the quality of dragon fruit which includes texture, moisture content, total dissolved solids, and total acid. Non-destructive color measurement used Chromameter to predict fruit maturity. Based on the results of this fruit maturity prediction, dragon fruit quality was predicted by using a regression model between fruit maturity and each quality parameter. Dragon fruit from various variations of maturity was used as a sample to find out its quality changes, and a regression equation was formed between the maturity of fruit and fruit quality. The results showed that along with the increasing maturity of dragon fruit, color (La * b *), texture, moisture content, and total dissolved solids changed following a cubic regression model. Color component